Respostas

A melhor resposta!
2014-07-03T14:53:31-03:00
a)2x(x+3)+9=0 \\ \\  \\  2 x^{2} +6x+9=0 \\  \\ \\  \Delta= 6^{2} -4*2*9  \\ \\ \Delta=36-72 \\ \\  \Delta=-36

S={Ф}, pois quando Δ<0, não existe zero real.



b)x(x-6)+8=0 \\ \\   x^{2} -6x+8=0 \\  \\  \\ \Delta=(-  6)^{2}-4*1*8  \\ \\ \Delta=36-32 \\  \\ \Delta=4  \\  \\ \\ x= \frac{-(-6)+- \sqrt{4} }{2*1}   \\ \\ x= \frac{6+-2}{2} \\   \\  \\ x'= \frac{6+2}{2}  \\  \\ x'= \frac{8}{2}  \\  \\ x'=4  \\  \\ \\ x''= \frac{6-2}{2}  \\  \\ x''= \frac{4}{2}  \\  \\ x''=2 \\ \\ \\ \\S=(2,4)
2 5 2
2014-07-03T15:10:40-03:00
a) 2x * (x+3)+9=0

 2 x² + 6x+9 = 0


► a = 2
► b = 6
► c = 9
 ∆² = b² - 4ac =

 (6)² - 4.2.9 =
36 - 4 . 18=576
► ∆ = √64
X = - b mais ou menos √64        ==> X = - 6 mais ou menos 8          
         2.a                                                            2.2


x' = - 6 + 8 ==> 2 :2 ==> 1
           4           4            2


 x" = - 6 - 8 ==> -14  :2==> -7
           4             4              2


b)  
 x * (x-6)+8=0  
  x² - 6x+8= 0
► a = 1
► b = -6
► c = 8
 ∆² = b² - 4ac =
(-6)² - 4.1.8 = 36 - 4 8=256
   ∆ = √16
 
x=- b mais ou menos √16      ==> X = 6 mais ou menos 4        
         2.a                                                            2    
x' = 6 + 4 ==> 10/2==> 5           2                 x" =  6 -4 ==> -2/4 ou 1/2                            2                                                                  2